2006
DOI: 10.1111/j.1440-1843.2006.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Serology of Chlamydia pneumoniae in patients with chronic cough

Abstract: Acute Chlamydia infection was more prevalent in patients with chronic cough, whereas chronic Chlamydia infection was not. There was no elevation of a systemic inflammatory marker in patients with chronic cough.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(42 reference statements)
0
3
0
1
Order By: Relevance
“…(2000), who used amoxicillin and erythromycin, this should have improved the performance of the trial therapy in culture negative patients since we thus covered more non‐mycobacterial pathogens, including ‘atypical’ agents such as Mycoplasma pneumoniae and Chlamydia pneumoniae , which are not covered by amoxicillin and can produce long episodes of cough (Vincent et al. 2000; Kim et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
“…(2000), who used amoxicillin and erythromycin, this should have improved the performance of the trial therapy in culture negative patients since we thus covered more non‐mycobacterial pathogens, including ‘atypical’ agents such as Mycoplasma pneumoniae and Chlamydia pneumoniae , which are not covered by amoxicillin and can produce long episodes of cough (Vincent et al. 2000; Kim et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In another study of 310 adolescent and adult patients with cough of 1- to 8-week duration (in Seoul and Incheon, 2009–2011), the pertussis positivity rate in culture, PCR, and serology tests was 1.0%, 3.2%, and 24.5%, respectively [70]. A case-control study found a positive association between acute Chlamydia pneumoniae infection and chronic cough [71]. However, in another study, only 1 of 68 patients with cough ≥3 weeks had a positive PCR for Chlamydia [42].…”
Section: Common Comorbidities In Adult Patients With Chronic Cough Inmentioning
confidence: 99%
“…In a case-control study, serological evidence of acute, but not chronic, infection of C. pneumoniae was more commonly found (25% vs. 5%) in 37 patients with chronic cough compared with agematched controls. 89 The journal also included two cases of recurrence of bronchiectasis after bilateral lung transplantation-a concern for future recipients. 90 Extending the use of Factor VIIa in haemophilia to a patient with diffuse alveolar haemorrhage from pulmonary-renal syndrome was demonstrated to be successful.…”
Section: Respiratory Infectionsmentioning
confidence: 99%